2011
DOI: 10.1016/j.neuroimage.2011.06.022
|View full text |Cite
|
Sign up to set email alerts
|

BOLD responses to different temporal frequency stimuli in the lateral geniculate nucleus and visual cortex: Insights into the neural basis of fMRI

Abstract: The neural basis of the blood oxygenation level dependent (BOLD) functional magnetic resonance imaging (fMRI) remains largely unknown after decades of research. To investigate this issue, the unique property of the temporal frequency tuning that could separate neural input and output in the primary visual cortex was used as a model. During moving grating stimuli of 1, 2, 10 and 20 Hz temporal frequencies, we measured 9.4-T BOLD fMRI responses simultaneously in the primary visual cortex of area 17 (A17) and are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
22
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 54 publications
8
22
1
Order By: Relevance
“…The lack of local energy stores in the brain requires that the vasculature respond dynamically to changes in neuronal activity, and it appears that this neurovascular coupling is also relatively conserved across species, although the timing and shape of the hemodynamic response vary (de Zwart et al, 2005). As expected based on these similarities, fMRI studies in cats, rodents, and monkeys have demonstrated patterns of activation in response to sensory stimuli similar to those detected in humans (Aksenov et al, 2015; Huang et al, 1996; Keilholz et al, 2004; Kim and Uğurbil, 1997; Lee et al, 1999; Logothetis et al, 2001; Schroeter et al, 2014; Yang et al, 1996; Yen et al, 2011). Likewise, using rs-fMRI researchers have shown that numerous networks (including somatosensory, motor, visual, and even “default mode”) are present across species (Belcher et al, 2016, 2013; Ghahremani et al, 2016; Lu et al, 2012; Mantini et al, 2011; Pawela et al, 2008; Schroeder et al, 2016; Vincent et al, 2007; Williams et al, 2010; Zhao et al, 2008).…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…The lack of local energy stores in the brain requires that the vasculature respond dynamically to changes in neuronal activity, and it appears that this neurovascular coupling is also relatively conserved across species, although the timing and shape of the hemodynamic response vary (de Zwart et al, 2005). As expected based on these similarities, fMRI studies in cats, rodents, and monkeys have demonstrated patterns of activation in response to sensory stimuli similar to those detected in humans (Aksenov et al, 2015; Huang et al, 1996; Keilholz et al, 2004; Kim and Uğurbil, 1997; Lee et al, 1999; Logothetis et al, 2001; Schroeter et al, 2014; Yang et al, 1996; Yen et al, 2011). Likewise, using rs-fMRI researchers have shown that numerous networks (including somatosensory, motor, visual, and even “default mode”) are present across species (Belcher et al, 2016, 2013; Ghahremani et al, 2016; Lu et al, 2012; Mantini et al, 2011; Pawela et al, 2008; Schroeder et al, 2016; Vincent et al, 2007; Williams et al, 2010; Zhao et al, 2008).…”
Section: Introductionsupporting
confidence: 62%
“…Their brains are small and unconvoluted, and their controlled genetic backgrounds result in high similarity across individual animals. Cats have more complex brains and a visual system that more closely approximates that of a human, and are widely used in visual studies (Moon et al, 2013; Yen et al, 2011). Nonhuman primates have the most complex brains and are the most costly to work with, but provide the closest approximation to the human brain and have provided key insights into the neurophysiology underlying the BOLD response (Hutchison and Everling, 2012; J.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, non-neuronal contributions to effects reported in these studies cannot be ruled out. Related to this point, when compared with multi-unit recordings or LFPs, the BOLD signal detected in fMRI is more greatly correlated with LFPs, reflecting a potential bias in fMRI for the detection of input activity rather than local cell spiking (Goense and Logothetis, 2008;Lippert et al, 2010;Logothetis et al, 2001;Yen et al, 2011). Although this relationship may not hold true at high spatial resolution (Kahn et al, 2013;Shih et al, 2013), it is worth noting that low-frequency LFP oscillations (1-1.5 Hz) may be increased during STN-DBS (Priori et al, 2006), with possible relevance for the activation profile detected with BOLD fMRI.…”
Section: Circuit Modulations During Deep Brain Stimulation At the Stnmentioning
confidence: 99%
“…Similar to other hemodynamics-based functional brain imaging techniques, the blood oxygenation level dependent (BOLD) fMRI signal is an indirect measurement of the neuronal activity. The exact relationship between the neuronal responses and hemodynamic responses remain unclear and under debates (Attwell et al 2002; Logothetis 2008; Vanzetta et al 2008; Enager et al 2009; van Eijsden et al 2009; Ekstrom 2010; Yen et al 2011). Indeed, in recent years there have been great efforts to resolve this controversial topic.…”
Section: Introductionmentioning
confidence: 99%